Metode USLE untuk Memprediksi Erosi Tanah dan Nilai Toleransi Erosi Sebuah Sistem Agricultural di Desa Genengan Kecamatan Jumantono Karanganyar - Komariah Komariah; Jaka Suyana (Universitas Sebelas Maret, 2015)
Erosion can potentially cause of land degradation. Prediction of erosion rate is needed on a certain plots of land so the sustainability of the farming system and appropriate conservation recommendations can be known. This research is intended to obtain information of erosivity value comparison in supporting erosion prediction acuracy USLE method to get erosion prediction value and erosion tolerated value (Etol). This information will be used to the determine the recommendations technology conservation on farming system of Genengan village, district Jumantono, Karanganyar Regency. A explorative descriptive research is using a land units map as the basic unit of analysis a survey in the field. The determination of sample unit is based on the land unit map from the overlay of land slope maps, land use maps, and soil maps on the land system Samin watershed. Results showed that the magnitude in Genengan Village on the land unit 1, land unit 2, land unit 5, land unit 6 and land unit 8 still under the tolerance value. Meanwhile land unit 3, land unit 4 and land unit 7 are exceeded the value this requires need for conservation. The suggested conservation is for the land unit 3 by planting 9 of vetiver between the main plant, where as on the land unit 4 and land unit 7 is recomended to apply 60% of straw mulch.